Pengembangan Sistem Downlink Data Adaptif Untuk Peningkatan Daya Jelajah Pesawat Tanpa Awak - Basukesti, Agus; Adiputra, Bangga Dirgantara (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
The main challenge for the development of unmanned aircraft today is the cruising range of unmanned aircraft. One of the causes of limited cruising range is the weakness of the communication system between aircraft and ground station. In this study designed a system of data downlink integrated with adaptive control so that it can increase cruising range from unmanned aircraft. The method used in this research is the experimental method to get the design and pilot plan downlink data system combined with adaptive control to create intelligent data downlink device that can increase cruising range unmanned aircraft. From this research found that Kalman Filter is the best algorithm used in designing an adaptive downlink system.